Floating Garbage Collector Based on OpenMV. Issue 3 (June 2021) - Yao, Chengkai
Abstract: Due to the high cost of human labor for maintenance, garbages in rivers often do not receive immediate cleaning, resulting in severe water pollution. Those floating garbages simultaneously strip the aesthetic of rivers and threaten the local marine ecosystem. Thence, we developed an unmanned vessel based on Arduino's platform, capable of auto-collecting garbage. The vessel includes two modes: the human operational mode allows individuals to manipulate the vessel and to collect garbages through Bluetooth connection; the auto-collecting mode is based on OpenMV's video processing function, enabling vessels to detect garbages nearby and transport the garbages into the vessel's interior through a rotating caterpillar track. At the end of this project, the vessel remains large rooms for improvements, such as increasing the efficiency and effectiveness of garbage collection and garbage detection. The vessel is suitable in small size rivers or ponds were artificial cleaning faces obstacles.